Identification of a Cluster of Extended-spectrum Beta-Lactamase–Producing Klebsiella pneumoniae Sequence Type 101 Isolated From Food and Humans. (10th August 2020) - Aguilar-Bultet, Lisandra; Bagutti, Claudia; Egli, Adrian; Alt, Monica; Maurer Pekerman, Laura; Schindler, Ruth; Furger, Reto; Eichenberger, Lucas; Roloff, Tim; Steffen, Ingrid; Huebner, Philipp; Stadler, Tanja; et al.
Abstract: We report a cluster of extended-spectrum beta-lactamase (ESBL)-producing Klebsiella pneumoniae sequence type 101, derived from 1 poultry and 2 clinical samples collected within the setting of a prospective study designed to determine the diversity and migration of ESBL-producing Enterobacterales between humans, foodstuffs, and wastewater.